2022
DOI: 10.54393/pbmj.v5i4.411
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices of Mothers Regarding Oral Hygiene and Dental Caries Among Children: A Systematic Review

Abstract: Oral hygiene is an important factor in determining good health especially among children. The role of mothers is inevitable in helping their children learn basics of maintaining good oral hygiene. However, the literature is unclear about the exact role and fulfillment of the learning outcomes about oral health given by the mother. Objective: To review knowledge, attitude and practices of mothers regarding oral hygiene and dental caries among children. Methods: Original observational studies of any sort, both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The better level of KAP about oral hygiene among mothers is directly related to better oral health and less chances of dental caries among their children (Al-Jaber et al, 2021). A systemic review also reported that children of mothers with poor KAP had higher risk of dental caries (Iqbal et al, 2022).…”
Section: Mothers Attitude Regarding Children's Oral Healthmentioning
confidence: 98%
“…The better level of KAP about oral hygiene among mothers is directly related to better oral health and less chances of dental caries among their children (Al-Jaber et al, 2021). A systemic review also reported that children of mothers with poor KAP had higher risk of dental caries (Iqbal et al, 2022).…”
Section: Mothers Attitude Regarding Children's Oral Healthmentioning
confidence: 98%
“…Higher oral health knowledge among mothers directly reduces the chances of dental diseases such as dental caries. However, this is only possible if mothers have enough knowledge about healthy oral habits and practices (Iqbal et al, 2022). Factors such as oral health literacy, age, education level of parents, socioeconomic level, practices, and parents' knowledge are linked with their optimal oral health and their children's oral health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Iqbal et al, (2022) regarding mothers' Knowledge, Attitudes, and Practices (KAP) found that only 24.9% had adequate knowledge, and 29% had poor attitudes toward their children's oral health. Therefore, a mother's KAP is the primary determinant of preventing the risk of oral disease as well as for optimal oral health of a child.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation